2014
DOI: 10.7860/jcdr/2014/9293.4453
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Hydroxylase 2 Gene Polymorphism in Anxiety and Depressive Disorder in Kashmiri Population

Abstract: Background: The gene of tryptophan hydroxylase is widely recognized as a major candidate gene in many psychiatric disorders. However, no study has been done which investigates tryptophan hydroxylase 2 gene polymorphism in anxiety and depressive disorders in Kashmiri population (India).Objectives: To study tryptophan hydroxylase 2 (TPH2) C 11993 A gene polymorphism in anxiety and depressive disorders.Method: Sixty patients of depression disorder, 60 patients of anxiety disorder and 40 unrelated healthy voluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
(16 reference statements)
0
5
0
1
Order By: Relevance
“…Since time immemorial, the valley of Kashmir has been regarded as the paradise on earth because of its splendid natural beauty. Over the last eighteen years, Kashmir valley has seen many downfalls, due to continuous violence, political turmoil, and reign of terror [ 1 , 2 , 15 ]. The last two decades have seen a rise of psychological and psychiatric disorders in Kashmir [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since time immemorial, the valley of Kashmir has been regarded as the paradise on earth because of its splendid natural beauty. Over the last eighteen years, Kashmir valley has seen many downfalls, due to continuous violence, political turmoil, and reign of terror [ 1 , 2 , 15 ]. The last two decades have seen a rise of psychological and psychiatric disorders in Kashmir [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown an association of TPH1 gene variants with depressive disorders [ 5 , 7 , 9 ]. Previously, in our earlier study, we found no relationship of another isoform of TPH gene (TPH2) in depressive disorders in Kashmiri (Indian) population [ 1 , 2 ]. As the association of TPH1 gene in depressive disorders in some studies has shown positive association and it was not possible to study all the variants of TPH 1 gene, due to financial and time restraints, TPH1 A779C variant was selected.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations